The Use of Gamification Media Based on Quiz Competitions (LCC) to Improve Understanding of the Qur'an and Hadith Subject in the Ninth Grade of MTs I'anatuth Tholibin Sukabumi - Euis Istikomah; Elsa Yunisa; Evi Mulyani; Maelasari Maelasari; Yati Supiyati; Adi Rosadi (Penerbit Hellow Pustaka, 2026)
Learning the Qur'an and Hadith in Islamic schools often faces challenges in maintaining student motivation and engagement because the methods used tend to be monotonous and teacher-centered. To overcome this, more engaging and interactive strategies are needed to actively engage students in understanding the values ​​of the Qur'an and Hadith. One relevant approach is gamification based on the Quiz Competition (LCC), which combines game elements such as competition, points, and awards into the learning process. This study aims to describe the process of implementing LCC gamification in Qur'an and Hadith learning, identify emerging obstacles, and assess the results and their impact on student understanding. The study used a descriptive qualitative method with observation, interview, and documentation techniques. The research subjects included Qur'an Hadith teachers, 30 ninth-grade students of MTs I'anatuth Tholibin Sukabumi, and the principal as an additional informant. The results showed that LCC increased student engagement, motivation, and understanding of the Qur'an Hadith material. Obstacles that emerged included time constraints and class control due to high student enthusiasm. The teacher overcame these by adjusting the time and more active class management. Overall, the implementation of LCC effectively created a competitive, enjoyable, and meaningful learning atmosphere for students.